Individual wire-length prediction with application to timing-driven placement. - Qinghua Liu
In this paper, we address the problem of individual wire-length prediction and demonstrate its usefulness in timing-driven placement. Many researchers have observed that different placement algorithms produce different individual wire lengths. We postulate that to obtain accurate results, individual wire-length prediction should be coupled with the placement flow. We embed the wire-length prediction into the clustering step of our fast placer implementation (FPI) framework . The predicted wire lengths act as constraints for the simulated annealing refinement stage, which guides the placement toward a solution fulfilling them. Experimental results show that our prediction process yields accurate results without loss of quality and incurs only a small cost in placement effort. We successfully apply the wire-length prediction technique to timing-driven placement. Our new slack assignment algorithm with predicted wire lengths (p-SLA) gives on average an 8% improvement in timing performance compared with the conventional modified zero-slack algorithm (m-ZSA).
Keywords: Annealing refinement stage; Clustering netlist; Fast placer implementation; Individual wire length prediction; Integrated circuit interconnections; Placement flow; Simulated annealing; Slack assignment algorithm; Timing driven placement